Are erythema nodosum-like lesions and superficial thrombophlebitis prodromal in terms of visceral involvement in Behcet's disease? - Coskun, B; Öztürk, P; Saral, Y (Wiley, 2005)
Erythema nodosum (EN)-like lesions and superficial thrombophlebitis (ST) are skin symptoms that are frequently observed in Behcet's disease. In most of the patients, skin symptoms precede serious visceral involvement. The study included 78 patients whose mean age was 33.48+/-6.16 (21-48). Of the cases, 37 were females and 41 were males. Forty-two patients (53.8%) had EN-like lesion and 12 (15.3%) had ST. Six of 54 patients, who had EN-like lesion and ST, were found to have no visceral involvement. In six of the remaining 48 patients, it was established that visceral involvement developed before lesions. It was found in 42 patients that these two lesions preceded visceral involvement. In addition, 18 of 24 patients who did not have these two lesions, do not still have visceral involvement. Therefore, we think that EN-like lesion and ST can be guiding in predicting serious visceral involvement and complications that can develop in advanced stages of Behcet's disease. (C) 2005 Blackwell Publishing Ltd.
Keywords: erythema nodosum - like lesions; superficial thrombophlebitis; Behcet's disease